Affective and social burdens of urban femininity: Reading the lyrics and digital reception of Paris Paloma’s Labour - Tirtakayana, Bilqis; Firdaus, Rima; Afdholy, Nadya (Yayasan Mitra Persada Nusantara, 2025)
This study explores the emotional and social burdens experienced by women within the context of urban culture, as represented in Paris Paloma’s song “Labour” and its reception on YouTube. The objective is to explore how feminist themes, particularly those related to gendered labor and emotional inequality, are articulated in digital music and audience responses. As digital platforms increasingly become sites of socio-cultural discourse, music consumption—especially songs with strong narrative lyrics—offers a space for expressing and recognizing shared gender-based experiences. The research employs a descriptive qualitative method, combining Sara Mills’ discourse analysis with Wolfgang Iser’s reader reception theory to explore both the textual and interpretive dimensions of meaning-making. The primary data includes the lyrics of “Labour” sourced from Genius.com and the three most liked YouTube comments within the last ten months. These comments were selected for their popularity and engagement, offering insight into how listeners emotionally and cognitively interact with the song. The analysis identifies “Labour” as a critique of patriarchal expectations in domestic relationships, symbolizing the unequal emotional and physical labor often assigned to women. The song's lyrical structure and metaphorical language frame the domestic sphere as a site of exploitation. Meanwhile, YouTube comments reveal a strong affective connection among female listeners, who share personal stories and expressions of solidarity, thereby reinforcing the song’s feminist message. In conclusion, “Labour” functions not only as a cultural artifact but also as a catalyst for digital feminist discourse, where music and social media together foster communal awareness and emotional validation.